Understanding the Footprint of the RBV in International Business Studies: the Last Twenty Years of Research - Ferreira, Manuel Portugal (2018)
International business (IB) research has evolved substantially over the past four decades incorporating new concerns and theoretical contributions. During the past two decades, the Resource-Based View (RBV) has gained the preference of many IB scholars and has gradually become one of the dominant theoretical perspectives for studying IB decisions and operations. The 1991 article “Firm resources and sustained competitive advantage” by Jay Barney is recognized as a fundamental contribution to the Resource-Based View (RBV). In this paper we assess the influence of the RBV, proxied by Jay Barney’s (1991) article, on IB research over the twenty years period, from 1991 to 2010. In this bibliometric study of the articles published in the leading journal for IB research – Journal of International Business Studies (JIBS) – we conduct citation and co-citation analyses, the networks of co-authorship, and delve into the analysis of the key research topics. Beyond understanding the extant research we also contribute to i identifying future research avenues.